Building Post-Disaster Psychosocial Resilience Through Toraja Cultural Animated Media in Teacher Training - Musfirah Musfirah; Imron Burhan; Harmelia Tulak; Topanus Tulak (Help: Journal of Community Service, 2026)
Indonesia's high vulnerability to natural disasters significantly impacts the psychological well-being of school-age children. While teachers play a strategic role in the recovery process, they often lack specialized psychosocial training. This community service aimed to enhance teachers' capacity to provide post-disaster child support by integrating resilience-building techniques with Toraja culture-based animated media. The Participatory Action Research (PAR) program was conducted at SDN 3 Buntao, involving 15 active teachers. The activity consisted of three systematic stages: preparation, implementation, and reflection. The implementation stage included presentations on fundamental resilience concepts, mentoring simulations, and hands-on practice in developing interactive animated videos using the Interacty application. The training resulted in a significant improvement in participants' understanding of identifying children's trauma symptoms and delivering appropriate emotional support, marked by a 75% increase in teacher confidence. Teachers successfully developed practical skills to produce culturally tailored animations and interactive quizzes. Integrating Toraja cultural elements into the digital media provided a highly positive impact, accelerating emotional closeness and making the psychosocial support more relatable for the students. This capacity-building initiative effectively empowered educators to deliver structured post-disaster psychological support. By combining evidence-based resilience strategies with culturally responsive digital tools, the training strengthens teachers' readiness to facilitate sustainable and engaging psychosocial recovery in the classroom.